Recent advances in the prevention and treatment of skin cancer using photodynamic therapy. Issue 11 (November 2010) - Zhao, Baozhong; He, Yu-Ying
Photodynamic therapy (PDT) is a noninvasive procedure that involves a photosensitizing drug and its subsequent activation by light to produce reactive oxygen species that specifically destroy target cells. Recently, PDT has been widely used in treating non-melanoma skin malignancies, the most common cancer in the USA, with superior cosmetic outcomes compared with conventional therapies. The topical 'photosensitizers' commonly used are 5-aminolevulinic acid (ALA) and its esterified derivative methyl 5-aminolevulinate, which are precursors of the endogenous photosensitizer protoporphyrin IX. After treatment with ALA or methyl 5-aminolevulinate, protoporphyrin IX preferentially accumulates in the lesion area of various skin diseases, which allows not only PDT treatment but also fluorescence diagnosis with ALA-induced porphyrins. Susceptible lesions include various forms of non-melanoma skin cancer such as actinic keratosis, basal cell carcinoma and squamous cell carcinoma. The most recent and promising developments in PDT include the discovery of new photosensitizers, the exploitation of new drug delivery systems and the combination of other modalities, which will all contribute to increasing PDT therapeutic efficacy and improving outcome. This article summarizes the main principles of PDT and its current clinical use in the management of non-melanoma skin cancers, as well as recent developments and possible future research directions.